Perceived Organizational Support and Workplace Conflict: The Mediating Role of Failure-Related Trust - Caesens, Gaëtane; Stinglhamber, Florence; Demoulin, Stéphanie; De Wilde, Matthias; Mierop, Adrien (Frontiers in Psychology, 2019)
The aim of the present research was twofold. First, we examined the effects of perceived organizational support on workplace conflict (i.e., relationship conflict and task conflict). Second, we identified one mechanism explaining these relationships, namely failure-related trust. Using a sample of 263 teachers from Belgium, the results of Study 1 indicated that perceived organizational support is negatively related to relationship conflict and is also, unexpectedly, negatively related to task conflict. Furthermore, using a sample of 477 Belgian employees, Study 2 replicated these results and further demonstrated that failure-related trust mediates the negative relationship between perceived organizational support and both types of workplace conflict. Theoretical and practical insights of this research are discussed.